Effects of repetitive or consecutive fasting-induced weight loss on glucose tolerance in rats fed high-fat diet - Yudai Nonaka; Makoto Inai; Shuhei Nishimura; Shogo Urashima; Shin Terada (Journal of Physical Fitness and Sports Medicine)
Weight loss reduces visceral fat and improves glucose tolerance. Our previous study found that weight loss from 3 consecutive days of fasting led to deteriorated glucose tolerance, but it is not clear whether this was due either to the physiological stress associated with consecutive fasting or fasting itself. This study aimed to compare the effects of repetitive or consecutive fasting on intra-abdominal fat mass and glucose tolerance in rats fed a high-fat diet. After 2 weeks of high-fat diet feeding, male Wistar rats were divided into three groups matched for body weight: one group continued to receive the high-fat diet ad libitum for 2 weeks (control, CON); the second group fasted for the last 3 days (consecutive fasting, CF); and the third group repeated 1-day fasting three times with a 6-day ad libitum feeding interval (repetitive fasting, RF). Compared to the CON group, the intra-abdominal fat mass was significantly lower in the CF group after the intervention period, and there was a tendency for lower values in the RF group. During the oral glucose tolerance test, plasma glucose levels were significantly higher in both fasting groups compared to the CON group, while levels in the CF group were significantly higher than in the RF group. Compared to the CON group, the CF group had significantly lower plasma insulin levels, and slightly lower levels in the RF group. These findings suggest that even when fasting days are dispersed over multiple occasions, insulin secretion capacity may decrease in a similar manner to consecutive fasting, leading to a deterioration in glucose tolerance.